2021
DOI: 10.1186/s13071-021-04961-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of molecular assays to detect Leishmania donovani in Phlebotomus argentipes fed on post-kala-azar dermal leishmaniasis patients

Abstract: Background Post-kala-azar dermal leishmaniasis (PKDL) caused by Leishmania donovani (LD) is a skin disorder that often appears after treatment of visceral leishmaniasis (VL) patients. PKDL patients are potential reservoirs of LD parasites, which can initiate a new epidemic of anthroponotic VL. Therefore, host infectiousness to its sand fly vector is a critical factor for transmission, and its accurate estimation can facilitate control strategies. At present, conventional microscopy serves as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 53 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…Isothermal amplification has been employed in the diagnosis of various parasitic diseases, addressing the challenges posed by traditional diagnostic methods [ 42 , 43 , 44 , 45 , 46 ]. Compared to PCR, isothermal amplification technology, exemplified by loop-mediated isothermal amplification (LAMP) and RPA, significantly reduces the reaction time and dependence on instruments.…”
Section: Application Of Nucleic Acid Amplification Tests In Parasite ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Isothermal amplification has been employed in the diagnosis of various parasitic diseases, addressing the challenges posed by traditional diagnostic methods [ 42 , 43 , 44 , 45 , 46 ]. Compared to PCR, isothermal amplification technology, exemplified by loop-mediated isothermal amplification (LAMP) and RPA, significantly reduces the reaction time and dependence on instruments.…”
Section: Application Of Nucleic Acid Amplification Tests In Parasite ...mentioning
confidence: 99%
“…Compared to PCR, isothermal amplification technology, exemplified by loop-mediated isothermal amplification (LAMP) and RPA, significantly reduces the reaction time and dependence on instruments. RPA is an efficient method for on-site detection due to its simple primer design, low-temperature requirements, and easy storage [ 43 , 44 ]. Recombinase-aid amplification (RAA), based on the same principle, also offers these advantages in rapid detection [ 47 ].…”
Section: Application Of Nucleic Acid Amplification Tests In Parasite ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the sand fly Phlebotomus papatasi in regions where L. major infections are common is likely to blame for the vast majority of reported cases of the disease in Saudi Arabia and other Arabian countries [ 13 ]. The zoonotic form of CL evolved as a result of the global expansion of leishmaniasis in the 20th century, with an estimated yearly incidence in Saudi Arabia of more than 4000 [ 14 , 15 ]. The widespread prevalence of desert rodents (reservoir animals) and sand flies is largely responsible for the endemic nature of CL in several regions in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…However, this test was not recommended for use by some studies [17]; or it was shown that it should be complemented by additional methods because of its low sensitivity [18]. Other POC format tools based on isothermal amplification were also developed [19][20][21][22][23][24]. Nevertheless, all these tools are generic and detect Leishmania parasites without identifying them.…”
Section: Introductionmentioning
confidence: 99%